Perception of Halal Cosmetics Consumers towards Halal Awareness in Online Social Network: Study in Malaysia and Indonesia - Respati, Titik; Jamilah, Lina; Alamsyah, Indra Fajar; Abdulhadi, Abdulrazak (UIN Sunan Gunung Djati Bandung, 2024)
The cosmetics and personal care industry has emerged as one of the most prominent and fastest-growing markets, especially among millennials worldwide. The halal cosmetics industry is also important to today's young generation. They and social media technology have become an important part of consumer research. This study explores the factors determining the millennial generation's choice of halal cosmetics. This study used the exploratory factor analysis (EFA) method with 202 millennial respondents from Indonesia and Malaysia. The Kaiser-Meyer-Olkin (KMO) test result is 0.723%, indicating a middling sampling. The Bartlett test result shows a value of 1848,828 with a significance level of 0.0000 < 0.05, indicating a correlation between the variables. There are no statements with a score of less than 0.5 after the communalities checking. As a result, every statement can be used more thoroughly in this research. Based on the results, six main factors can increase the millennial generation's interest in making choices about halal cosmetics: social media campaign, influencer trustworthiness, halal awareness, brand curiosity in social media, cosmetics advertisement language, and brand trust and product quality.